2016
DOI: 10.21037/cdt.2016.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia impacts leukocyte kinetics after cardiac arrest

Abstract: Background: Patients admitted to the hospital after primarily successful cardiopulmonary resuscitation (CPR) are at a very high risk for neurologic deficits and death. Targeted temperature management (TTM) for mild therapeutic hypothermia has been shown to improve survival compared to standard treatment.Acute cardiovascular events, such as myocardial infarction (MI), are a major cause for cardiac arrest (CA) in patients who undergo CPR. Recent findings have demonstrated the importance and impact of the leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(49 reference statements)
2
4
1
Order By: Relevance
“…Bro-Jeppesen and Dufner reported that hypothermia treatment could lead to a decrease in the number of white blood cells and neutrophils[ 27 , 28 ], which is consistent with the results of our study. However, the relationship between hypothermia and platelet count is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Bro-Jeppesen and Dufner reported that hypothermia treatment could lead to a decrease in the number of white blood cells and neutrophils[ 27 , 28 ], which is consistent with the results of our study. However, the relationship between hypothermia and platelet count is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Bro-Jeppesen and Dufner reported that hypothermia treatment could lead to a decrease in the number of white blood cells and neutrophils [22,23], which is consistent with the results of our study. However, the relationship between hypothermia and platelet count is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory response after achieving return of spontaneous circulation might mimic a real infection 31 and MTH influences body temperature, inflammatory parameters, and leukocyte count. 32 However, in our population the leucocyte count integrated in the diagnostic process was not significantly different between MTH/NT. We defined our diagnostic criteria in accordance to VAP, as independently associated with less microbiological confirmation.…”
Section: Leucocyte Count Max [G/l] Median (Iqr)contrasting
confidence: 60%
“…Especially in our population of CA patients treated with hypothermia, diagnostic criteria might be confounded. Inflammatory response after achieving return of spontaneous circulation might mimic a real infection 31 and MTH influences body temperature, inflammatory parameters, and leukocyte count 32 . However, in our population the leucocyte count integrated in the diagnostic process was not significantly different between MTH/NT.…”
Section: Discussionmentioning
confidence: 51%